2016
DOI: 10.11002/kjfp.2016.23.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of detoxified Rhus verniciflua vinegar fermented using different acetic acid bacteria

Abstract: To investigate the effect of different acetic acid bacteria on qualities of detoxified Rhus verniciflua vinegar (DRV), different DRVs were produced by using three acetic acid bacterial strains including Acetobacter pasteurianus KACC16934 (AP), Acetobacter malorum V5-7 (AM), and Gluconoacetobacter entanii RDAF-S (GE). Little difference in pH (2.87~2.90) or titratable acidity (5.33~5.68%) was observed among different DRVs. Acetic acid yields of the AP, AM, and GE strains were 78.6%, 85.3%, and 85.9%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Nineteen genera of AAB, including Acetobacter, Gluconobacter, Gluconacetobacter, and others, have been recognized based on the results of genetic analysis and their respective characteristics [2]. The presence of AAB has been detected in a variety of foods; Acetobacter aceti (A. aceti), Acetobacter pasteurianus (A. pasteurianus), Acetobacter malorum (A. malorum), and Acetobacter pomorum (A. pomorum) are the most frequently isolated species in the process of vinegar fermentation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen genera of AAB, including Acetobacter, Gluconobacter, Gluconacetobacter, and others, have been recognized based on the results of genetic analysis and their respective characteristics [2]. The presence of AAB has been detected in a variety of foods; Acetobacter aceti (A. aceti), Acetobacter pasteurianus (A. pasteurianus), Acetobacter malorum (A. malorum), and Acetobacter pomorum (A. pomorum) are the most frequently isolated species in the process of vinegar fermentation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Various physiological activities, such as anti-cancer and antioxidant studies (Kwak et al, 2005;Park et al, 2000), anti-mutagenic effects (Park et al, 2004), and anti-thrombotic effects (Jeon et al, 2006) have been reported in R. verniciflua application studies. In addition to functional studies, studies on the reduction of urushiol for use as food have also been reported (Baek et al, 2015;Baek et al, 2016;Choi et al, 2013); however, most studies have focused on the xylem.…”
mentioning
confidence: 99%